Konsep Negara Menurut Imam Ayatullah Khomeini dalam Tinjauan Filsafat Politik - Sansan Muhammad (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Government in Islam has long historical roots, starting from the reign of the Prophet, the companions, the tabi'in, to the Imams. The purpose of this paper is to describe the main discussion of the research on the concept of the state according to Imam Ayatullah Khomeini and the analysis of Islamic political philosophy on the thoughts of Imam Ayatollah Khomeini. This research is a literature study, with qualitative methods, and Islamic political philosophy as a knife of analysis. The finding in this study is that the concept of the state in Khomeini's view is a system of government through the leadership of the ulama (Wilayah al-Faqih). Which in the al-Faqih Region government system, monotheism is the basis of the law. This theory is at the core of Khomeini's thoughts on the concept of the Islamic State. This concept is the result of his reinterpretation of the Islamic political system that the Prophet had built, which was then continued by the Imams to Imam Mahdi. Iran's democracy is a “theo-democracy”, and not a democracy as practiced by other democracies. However, the point that needs to be underlined is that Faqih's position cannot be applied arbitrarily, but rather to control democracy, so that it remains in line with Islamic values and the mandate of the Islamic Revolution of Iran.